Security analysis - Graham, Benjamin, 1894-1976.; Dodd, David L.( 1895-1988.) (New York: McGraw-Hill, 1996)
Explains financial analysis techniques, shows how to interpret financial statements, and discusses the analysis of fixed-income securities and the valuation of stocks.
Reprint of first ed. Originally published: New York : Whittlesey House, 1934.
Includes index.
Keywords: Speculation; Securities -- -- United States; Dividendes; Investissements; Valeurs mobili?eres -- -- Cours; Spéculation.; Investment analysis